(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the nutritional status and related factors among postoperative ovarian cancer patients at Vietnam National Cancer Hospital, 2025-2026. Subjects and methods: A cross-sectional study was conducted on 125 ovarian cancer patients on the 7th day after surgery during inpatient treatment at the Gynecologic Surgery Department and the On-Demand Treatment Department of Vietnam National Cancer Hospital. Results: The prevalence of postoperative malnutrition according to GLIM criteria was 79.2%. Malnutrition based on BMI was observed in 23.2% of patients, while the prevalence of overweight/obesity was 4%. Serum albumin-defined malnutrition was found in 33.8% of cases. The prevalence of anemia was 44.8%. Patients living in rural areas had a 2.95-fold higher risk of malnutrition compared to those living in urban areas (OR = 2.95; 95% CI: 1.01-8.56; p < 0.05), and this difference was statistically significant. Conclusion: Postoperative malnutrition is highly prevalent. Place of residence is an independent factor associated with patients’ nutritional status. Timely and appropriate nutritional assessment, counseling, and intervention are essential to improve postoperative nutritional outcomes.